2022
DOI: 10.1007/s12185-022-03300-4
|View full text |Cite
|
Sign up to set email alerts
|

Low clinical protective response to SARS-CoV-2 mRNA COVID-19 vaccine in patients with multiple myeloma

Abstract: We conducted a prospective, three-center, observational study in Japan to evaluate the prevalence of seropositivity and clinically protective titer after coronavirus disease 2019 vaccination in patients with plasma cell dyscrasia(PCD). Two-hundred sixty-nine patients with PCD [206 symptomatic multiple myeloma (MM)] were evaluated. Seropositivity was observed in 88.7% and a clinically protective titer in 38.3% of MM patients, both of which were significantly lower than those of healthy controls. Patients receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 25 publications
(43 reference statements)
1
17
0
Order By: Relevance
“…Using commercially available anti‐spike antibody testing, we observed that ~85% of our patients with PCD mounted a positive serological response within 6 months of completing the initial vaccination series, comparable to other previous studies 11–18 . In studies assessing neutralising antibodies, the serological response has been lower, ranging from 41% to 74% 12,19–22 .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Using commercially available anti‐spike antibody testing, we observed that ~85% of our patients with PCD mounted a positive serological response within 6 months of completing the initial vaccination series, comparable to other previous studies 11–18 . In studies assessing neutralising antibodies, the serological response has been lower, ranging from 41% to 74% 12,19–22 .…”
Section: Discussionsupporting
confidence: 81%
“…Using commercially available anti‐spike antibody testing, we observed that ~85% of our patients with PCD mounted a positive serological response within 6 months of completing the initial vaccination series, comparable to other previous studies. 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 In studies assessing neutralising antibodies, the serological response has been lower, ranging from 41% to 74%. 12 , 19 , 20 , 21 , 22 Although the presence and titre of neutralising antibodies may more directly reflect viral protection, these assays are not widely available in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Our results also imply an inferior response among anti-CD38 therapy recipients. A negative impact of anti-CD38 therapy on vaccine efficacy was previously described by some studies [ 29 , 36 , 37 ] and denied by another [ 38 ]. However, it may be difficult to draw either conclusion from our results due to the underrepresentation of multiple myeloma in our cohort and because other effects of concomitant treatments, such as immunomodulatory drugs were not analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a growing body of studies suggests that the humoral response to COVID-19 vaccination may be suboptimal among a group that include people with hematological malignancies [ 1 , [17] , [18] , [19] , [20] ], chronic kidney failures [ 21 , 22 ], and organ transplant recipients [ [23] , [24] , [25] , [26] , [27] ]. Moreover, the degrees of impairment of the serological response within an at-risk group are often dependent on the treatment status and timing of vaccination [ [28] , [29] , [30] , [31] ], implying that risk-based vaccination is required. Although many of these studies help raise the alert to the poorer humoral response of at-risk individuals in comparison to healthy individuals, comparative risk analyses between the high-risk groups seems to be rather limited.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported the longitudinal humoral response after the second (D2) and third-doses (D3) of mRNA vaccination in consecutive patients with HD and compared it to that of health care workers (HCW). 13,14 We measured the anti-SARS-CoV-2 antibody titers of spike antigen (anti-S) and nucleocapsid antigen (anti-N) (Elecsys Anti-SARS-CoV-2 ECLIA, Roche Diagnostics, Burgess Hill, UK) after second dose (post-D2), before (pre-D3) and after third dose (post-D3) vaccination between July 2021 and September 2022. In this study, we investigated the incidence of newly con rmed Omicron breakthrough infection among the fully vaccinated (≥ D2) participants from January 1 through September 30, 2022.…”
Section: Participantsmentioning
confidence: 99%